Leptopus hispanus and Erianotus lanosus: the first DNA-assisted records of Leptopodidae (Hemiptera, Heteroptera) for the fauna of Georgia - Beka Chitadze; Eka Arsenashvili; Natalia Bulbulashvili (Caucasiana, 2023)
The shore-bug (Leptopodidae Brullé, 1836) family is reported from Georgia for the first time upon several finds of Leptopus hispanus Rambur, 1840, and Erianotus lanosus (Dufour, 1834) (Hemiptera, Heteroptera). These species are widespread from the Mediterranean to Central Asia, including the Caucasus. Barcodes of the species, collecting information, and pictures of specimens are given.